Reactions of a diborylstannylene with CO2 and N2O: diboration of carbon dioxide by a main group bis(boryl) complex. Issue 26 (11th May 2021) - Protchenko, Andrey V.; Fuentes, M. Ángeles; Hicks, Jamie; McManus, Caitilín; Tirfoin, Rémi; Aldridge, Simon
Abstract : Reactions of a bis(boryl) tin complex towards carbon dioxide proceed via insertion into the Sn–B bond(s), with subsequent B–O reductive elimination leading to the net diboration of CO2 . Abstract : The reactions of the boryl-substituted stannylene Sn{B(NDippCH)2 }2 (1 ) with carbon dioxide have been investigated and shown to proceed via pathways involving insertion into the Sn–B bond(s). In the first instance this leads to formation of the (boryl)tin(ii ) borylcarboxylate complex Sn{B(NDippCH)2 }{O2 CB(NDippCH)2 } (2 ), which has been structurally characterized and shown to feature a κ 2 mode of coordination of the [(HCDippN)2 BCO2 ] − ligand at the metal centre. 2 undergoes B–O reductive elimination in hexane solution (in the absence of further CO2 ) to give the boryl(borylcarboxylate)ester {(HCDippN)2 B}O2 C{B(NDippCH)2 } (3 ) i.e. the product of formal diboration of carbon dioxide. Alternatively, 2 can assimilate a second equivalent of CO2 to give the homoleptic bis(borylcarboxylate) Sn{O2 CB(NDippCH)2 }2 (4 ), which can be prepared via an alternative route from SnBr2 and the potassium salt of [(HCDippN)2 BCO2 ] −, and structurally characterized as its DMAP ( N, N -dimethylaminopyridine) adduct. Structural and reactivity studies also point to the possibility for extrusion of CO from the [(HCDippN)2 BCO2 ] − fragment to generate the boryloxy system [(HCDippN)2 BO] −, a ligand which can be generated directly from 1 via reaction with N2 O. The initially formed unsymmetrical species Sn{B(NDippCH)2 }{OB(NDippCH)2 } has been shown to be amenable to crystallographic study in the solid state, but to undergo ligand redistribution in solution to generate a mixture of 1 and the bis(boryloxy) complex Sn{OB(NDippCH)2 }2 .